(untitled) (Plant Tissue Culture and Biotechnology, 2024)
Turmeric (Curcuma longa) is used as a spice and has excellent medicinal value. However, the field multiplication rate of turmeric plants is not satisfactory. In vitro methods could be a feasible alternative to vegetative propagation in the field. This study was aimed at developing a suitable protocol for the clonal propagation of turmeric confirming the genetic fidelity of the in vitro regenerated plantlets. The explants of shoot bud (full, half, and quarter), root, rhizome, and leaf were cultivated on MS medium with BAP, NAA, and Kinetin. Cultured shoot buds showed a higher regeneration frequency and shoots per explant than those obtained from other explants. The highest shoot regeneration was 72.49% from shoot buds, followed by rhizome (68.76%) and the lowest was 53.93 % from ¼ shoot buds. There were significant effects of growth regulator combinations and concentrations in shoot regeneration from shoot bud explant. The highest shoot regeneration per shoot bud explant was 4.42 with BAP at 20.0 mg/l and NAA at 0.5 mg/l at 24 weeks. The best rooting response with 9.75 roots per explant was reported with 1.0 mg/l BAP with 1.0 mg/l NAA. The rooted plants were successfully transferred to pots for their acclimatization. Both the micropropagated shoots and their mother plant produced monomorphic bands with the six RAPD markers that confirm the genetic fidelity of micropropagated clones. These results showed that in vitro raised plantlets of turmeric had no risk of somaclonal variations and were found to be true-to-type in nature over the culture period. The protocol developed through this investigation has the potential application for the rapid multiplication of turmeric plants. Plant Tissue Cult. & Biotech. 34(1): 55-69, 2024 (June)